A case of breast carcinoma presenting as carcinoma en cuirasse - Irem Genç; Seray Külcü Çakmak; Emine Tamer; Servet Güreşçi; Devrim Tuba Ünal (Our Dermatology Online, 2018)
Carcinoma en cuirasse is a rare and unique form of cutaneous metastases, which surrounds the trunk in a firm and leathery fibrotic fashion, like an armor. We report a case of carcinoma en cuirasse in a 53-years-old female patient who was admitted to Dermatology outpatient clinic with pruritic, red, firm papules and plaques on the left breast and arm, extending to upper abdomen and medial part of right breast. At time of admission the patient did not have a history of an internal malignancy. Histopathological diagnosis of the incisional biopsy material from the plaque lesion was consistent with invasive ductal carcinoma. Imaging studies showed axillary, paraaortic, aortocaval lymph node involvement, pleural effusion, lung and liver metastases. The patient was referred to Medical Oncology Department and was treated with cyclophosphamide and adriamycine chemotherapy. This case of carcinoma en cuirasse preceeding the diagnosis of metastatic breast carcinoma and leading to diagnosis of malignancy is rare and important. Prognosis depends on the type of primary tumor and it's biological behavior, predictably, poor prognosis is expected in this case of metastatic invasive ductal carcinoma.